Technical report: the approximation solution of linear Black-Scholes equation by numerical method / Nur Alleysa Md Isa, Fatin Shakirah Leman and Nurhidayah Yahya - Md Isa, Nur Alleysa; Leman, Fatin Shakirah; Yahya, Nurhidayah (2017)
Linear Black Scholes model is a partial differential equation in financial mathematics. This report is discussed about a solution method for the Black Scholes model with too European options call as boundary problem numerically. For numerical approximation, a weighted average method was used to solve the model by using different weights. Firstly, the approximation solution was obtained by using a Finite Different Method then followed by a weighted average technique. After that, the numerical results for the European Call options was presented. The results for the Finite Different method showing that if there is increasing in time, the value of the options, V (S, t) also increases but value of the options have the different results when using a weighted average method. Finally, the research continue by doing some changes in parameter of Black Scholes to determine the value of the options